Determinants of green consumer behavior: A case study from Vietnam - Luan Trong Nguyen; Tri Huu Nguyen; Han Ngoc Nguyen; Loi Dai Nguyen; Dao Thi Thu Nguyen; Linh Duy LE (Cogent Business & Management, 2023)
The rapid upward thrust of the economy has harmed the environment, which has been compounded by pollution. More and more people are becoming concerned about their surroundings and looking for strategies to mitigate their unfavorable consequences. This is seen in governments' and enterprises' determination to expand and produce environmentally friendly products, as well as raise demand for green products. The purpose of this research is to uncover characteristics influencing green consumption behavior in Vietnam and to determine the most powerful motivator that drives customers to buy green products. The quantitative technique was applied in this investigation, with 231 samples obtained via an online survey. To analyze and assess the acquired data, several methods such as Cronbach's Alpha, EFA, SEM, One-way ANOVA, and Independent Sample T-test were used using SPSS and Amos software. According to the findings, three elements, including Attitudes, Social Norms, and Environmental Concerns, have a beneficial effect on green consumption behavior in Vietnam, with environmental concerns playing a particularly important role. The latest findings offered meaningful data about buyer purchasing characteristics, allowing businesses to expand green goods and devise marketing practices to get more customers to make use of them.
Keywords: M10; A10; D20; F60; 650; TPB; Green consumption; green products; marketing practices